PENERAPAN SISTEM PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM DAERAH (BLUD) PADA UNIT ORGANISASI PEMERINTAHAN DAERAH KABUPATEN MUSI RAWAS - Martini Martini; Sardiyo Sardiyo; Reza Septian (Jurnal Interprof, 2021)
The Musi Rawas Regency Government as an extension of the Central Government is the executor of the development that is being carried out in order to improve the welfare of the community, so its implementation must be optimal where to make it happen it needs proportional budget support sourced from the Musi Rawas Regency APBD. One of the important factors in formulating and determining the APBD is Regional Original Revenue (PAD), where another scheme that allows to obtain PAD is through the implementation of BLUDs in order to improve public services in their work units. Since 2018 until now, the Musi Rawas Regency Government has formed 19 UPTs. All of the UPTs that were formed were one that had implemented the pattern of BLUD financial governance, namely the UPT for the Drinking Water Supply System at the Public Works Office of CK, Spatial Planning and Irrigation in Musi Rawas Regency. This study raises two strategic issues, namely what UPTs can implement the BLUD Financial Governance Pattern and how the mechanism of the Work Unit/UPTD transforms to implement the BLUD Financial Governance Pattern. The method approach used in this study is a qualitative approach where the data sources used in this study are primary data and secondary data. Primary data obtained from the results of a survey or Focus Group Discussion (FGD) with respondents (representations from related work units, communities and related organizational groups) shows that there are 13 UPTDs that apply BLUD as a pattern of financial management of their work units and five UPTDs have not been able to implement BLUD as the pattern of financial management of the work unit with details of three UPTDs that have no regional revenue performance and two UPTDs are public services related to taxes, levies and certain permits.